The IL-6/STAT3 Signaling Pathway Is an Early Target of Manuka Honey-Induced Suppression of Human Breast Cancer Cells - Aryappalli, Priyanka; Al-Qubaisi, Sarah S.; Attoub, Samir; George, Junu A.; Arafat, Kholoud; Ramadi, Khalil B.; Mohamed, Yassir A.; Al-Dhaheri, Mezoon M.; Al-Sbiei, Ashraf; Fernandez-Cabezudo, Maria J.; al-Ramadi, Basel K. (Frontiers in Oncology, 2017)
There is renewed interest in the potential use of natural compounds in cancer therapy. Previously, we demonstrated the anti-tumor properties of manuka honey (MH) against several cancers. However, the underlying mechanism and molecular targets of this activity remain unknown. For this study, the early targets of MH and its modulatory effects on proliferation, invasiveness, and angiogenic potential were investigated using two human breast cancer cell lines, the triple-negative MDA-MB-231 cells and ER-positive MCF-7 cells, and the non-neoplstic breast epithelial MCF-10A cell line. Exposure to MH at concentrations of 0.3% to 1.25% (w/v) induced a dose-dependent inhibition of the proliferation of MDA-MB-231 and MCF-7, but not MCF-10A, cells. This inhibition was independent of the sugar content of MH as a solution containing the same concentrations of its three major sugars failed to inhibit cell proliferation. At higher concentrations (>2.5%), MH was found to be generally deleterious to the growth of all three cell lines. MH induced apoptosis of MDA-MB-231 cells through activation of caspases 8, 9, 6, and 3/7 and this correlated with a loss of Bcl-2 and increased Bax protein expression in MH-treated cells. Incubation with MH induced a time-dependent translocation of cytochrome c from mitochondria to the cytosol and Bax translocation from the cytosol into the mitochondria. MH also induced apoptosis of MCF-7 cells via the activation of caspases 9 and 6. Low concentrations of MH (0.03%-1.25% w/v) induced a rapid reduction in tyrosine-phosphorylated STAT3 (pY-STAT3) in MDA-MB-231 and MCF-7 cells. Maximum inhibition of pY-STAT3 was observed at 1 hr with a loss of >80% and coincided with decreased IL-6 production. Moreover, MH inhibited the migration and invasion of MDA-MB-231 cells as well as the angiogenic capacity of HUVECs. Our findings identify multiple functional pathways affected by MH in human breast cancer and highlight the IL-6/STAT3 signaling pathway as one of the earliest potential targets in this process.